AKSI DAN REAKSI REGULATOR DAN LEGISLATOR PEMERINTAH DAERAH KOTA “SP” TERHADAP PAJAK KARBON - Yosefani, Rahel; Hastuti, M. E. (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This research aims to describe the mechanism of carbon trading until finally a carbon tax appears. The researcher used legislators and the Surabaya city government. The researcher analyzes how the government and legislators support the implementation of the carbon tax that will be implemented in 2025. The perception of the value-belief-norm theory of carbon tax can be included in 3 basic principles of value. However, the Surabaya government still fulfills 1 principle, namely altruistic value. Carbon taxes form a person's belief that the relationship between humans and ecosystems is important to maintain.Keywords : carbon tax, carbon trading, value-belief-norm theory, legislator, government